Penguatan Kemampuan Belajar Berbasis Masjid - Siti Anah Kunyati; Reviandari Widyatiningtyas (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
The Community Service Activity (Pengabdian Kepada Masyarakat (PKM)) at Balong Gede District, Bandung City, especially Baitul Kiran Mosque, is an area on the border of Cikapundung River. Baitul Kiran Mosque resides in area that does not have a legal permit. The surrounding community has long lived in slums, poverty, and tends to neglect both religious and general education. One of activity to be carried out is to resolve learning difficulties of children with a mosque-based program to strengthen learning abilities. This program  carried out using method of focus group discussing, tutoring, and counseling to build motivation of education. The success of the PKM activities are: (1) strengthening of general education and understanding of religion that (a) students are motivated to take part in tutoring activities, (b) the learning difficulties of children in school are overcome by completing homework from school, and (c) learning patterns are better with tutoring activities twice a week; (2) strengthening the function of the mosque which are besides being a means of worship, but also an educational facility for strengthening learning activities of kindergarten, elementary, and junior high school students.